A COGNITIVE MODEL OF BULLY-VICTIM INTERACTIONS - García Orza, Javier (Anales de Psicología / Annals of Psychology)
Bullying is a subtype of aggression that involves systematic verbal, psychological or physical harassment of a weaker child (the whipping boy) by a stronger one (the bully). This behavior is elicited by subjects with the proposal of stablishing a dominance relation wich provides them social or individual rewards. This aggression used to ocurr with considerable frequency between pupils in the school. Bullying is a complex interaction in wich educatives, socials and cognitives variables are involved. The aim of this review is to offer, from a socialcognitive perspective wich proposed the use of mental models of interpersonal relationship, an analysis of the processes implicated in the interaction between bullies and victims. Attention to bullying from this point of view can facilitate the understanding of the phenomena wich will redounds to intervention and prevention.